2006
DOI: 10.1590/s1677-55382006000100007
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer pathologic stage pT2b (2002 TNM staging system): does it exist?

Abstract: Using the point-count method for tumor extent, our study questions a real existence for pathologic stage pT2b tumors (unilateral tumors involving greater than one-half of one lobe).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…The same result was reported by others who used a pathological assessment [10,11]. In the first study, RP specimens of 369 patients with prostate cancer were evaluated by complete embedding and whole‐mount processing [10]; no pathological pT2b tumour specimen was found.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The same result was reported by others who used a pathological assessment [10,11]. In the first study, RP specimens of 369 patients with prostate cancer were evaluated by complete embedding and whole‐mount processing [10]; no pathological pT2b tumour specimen was found.…”
Section: Discussionsupporting
confidence: 61%
“…The latter study by Quintal et al. [11] used a point‐counting method, i.e. each quadrant of each whole‐mount section was drawn on paper and contained eight equidistant points.…”
Section: Discussionmentioning
confidence: 99%
“…Also, defining pathological tumour stage according to uni‐ or bilateral lobe involvement may not be optimal for prostate cancer, which frequently present as a multifocal tumour. Moreover, some Western researchers have reported that pT2b prostate cancers (according to the 1992 and the 2002 TNM staging systems) actually do not exist [5,6]. Meanwhile, to our knowledge, the current TNM staging system for prostate cancer has not been evaluated formally in an Asian series of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Biyokimyasal nüksü öngörmede T2 alt sınıflamasının katkısının değerlendirildiği başka bir çalışmada, ameliyat öncesi PSA ve patolojik Gleason skorunun 7 ve 8-10 olması biyokimyasal nüks bakımından öngörücü iken, patolojik T2 alt gruplarının herhangi bir katkısının olmadığı bulunmuştur. [19] 2002 TNM sınıflamasına göre pT2b tümörlerin saptanma oranı çalışmaların çoğunda çok düşüktür, [20][21][22] hatta bazı çalışmalarda hiç saptanmamıştır. [14] Farklı olarak bir çalışmada prostata sınırlı tümörlerin %61.1'inin pT2b olduğu bulunmuştur.…”
Section: Discussionunclassified
“…Brezilya'dan yapılan bir çalışmada da pT2b tümör saptanmamıştır. [22] Tümör hacminin prognostik önemi konusunda tartışma yoktur, ancak kullanılmakta olan parametrelerin (evre, Gleason skoru, seminal vezikül invazyonu, cerrahi sınır) ek katkı sağlayıp sağlamadığı tartışmalıdır. Katkı sağlamasa da tespit edilmesi önerilebilir.…”
Section: Discussionunclassified